International Center for Agricultural Research in the Dry Areas (ICARDA) Intellectual Property Policy - International Center for Agricultural Research in the Dry Areas (CGIAR System Organization, 2014)
ICARDA now adopts the following policy on the management of intellectual property (“Policy”). This Policy shall be read in conjunction with the IA Principles and does not contain anything that contradicts the IA Principles. Should any contradictions arise, the IA Principles shall prevail over this Policy.